Establishing Tetraploid Embryogenic Cell Lines of Magnolia officinalis to Facilitate Tetraploid Plantlet Production and Phenotyping - Gao, Yanfen; Ma, Junchao; Chen, Jiaqi; Xu, Qian; Jia, Yanxia; Chen, Hongying; Li, Weiqi; Lin, Liang (Frontiers in Plant Science, 2022)
The production of synthetic polyploids for plant breeding is compromised by high levels of mixoploids and low numbers of solid polyploid regenerants during in vitro induction. Somatic embryogenesis could potentially contribute to the maximization of solid polyploid production due to the single cell origin of regenerants. In the present study, a novel procedure for establishing homogeneous tetraploid embryogenic cell lines in Magnolia officinalis has been established. Embryogenic cell aggregate (ECA) about 100-200 µm across, and consisting of dozens of cells, regenerated into a single colony of new ECAs and somatic embryos following colchicine treatment. Histological analysis indicated that the few cells that survived some colchicine regimes still regenerated to form a colony. In some colonies, 100% tetraploid somatic embryos were obtained without mixoploid formation. New granular ECA from single colonies with 100% tetraploid somatic embryos were isolated and cultured individually to proliferate into cell lines. These cell lines were confirmed to be homogeneous tetraploid by flow cytometry. Many tetraploid somatic embryos and plantlets were differentiated from these cell lines and the stability of ploidy level through the somatic embryogenesis process was confirmed by flow cytometry and chromosome counting. The establishment of homogeneous polyploid cell lines, which were presumed to represent individual polyploidization events, might expand the phenotypic variations of the same duplicated genome and create novel breeding opportunities using newly generated polyploid plantlets.